2019
DOI: 10.32098/mltj.01.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of De Quervain’s tenosynovitis and its association with SMS texting

Abstract: Objective: to assess the frequency of De Quervain's tenosynovitis and its association with SMS texting. Method: a cross-sectional survey was conducted among undergraduate students studying in different physical therapy schools of Karachi belonging to both public and private sectors. Sample size was 300 students which were selected through convenience sampling. Data was collected through self-administered questionnaire and severity of the pain was assessed through Universal Pain Assessment Tool and De Quervain'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
13

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 17 publications
5
42
0
13
Order By: Relevance
“…Despite the convenience of mobile phones, however, the related adverse effects associated with problematic mobile phone use (PMPU) are noteworthy. PMPU has been broadly defined as the inability to regulate one's use of the mobile phone, which eventually involves negative consequences in daily life [9], including somatic discomfort [10,11], sleep disturbance [12,13], negative emotions and stress [14][15][16][17][18][19], poor academic performance [20,21], low self-esteem [22,23], and accidental injuries (e.g., motor vehicle accidents [24], bicycle crashes/near crashes [25], pedestrian collisions, and falls [26]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the convenience of mobile phones, however, the related adverse effects associated with problematic mobile phone use (PMPU) are noteworthy. PMPU has been broadly defined as the inability to regulate one's use of the mobile phone, which eventually involves negative consequences in daily life [9], including somatic discomfort [10,11], sleep disturbance [12,13], negative emotions and stress [14][15][16][17][18][19], poor academic performance [20,21], low self-esteem [22,23], and accidental injuries (e.g., motor vehicle accidents [24], bicycle crashes/near crashes [25], pedestrian collisions, and falls [26]).…”
Section: Introductionmentioning
confidence: 99%
“…Modern life style escalated the incidence of De Quervain tenosynovitis because of computer and cellular phones excessive use [11].…”
Section: Epidemiologymentioning
confidence: 99%
“…Their results suggested that high volume texting may be a risk for thumb tendinopathy. Equally, Ali et al [59] and Eapen et al [60] associated intense texting with a heightened risk for musculoskeletal disorders of the thumb and wrist. Inal et al [61] demonstrated somewhat enlarged median nerves in high frequent smartphone users, due to the repetitive wrist flexion and extension during smartphone use.…”
Section: Discomfort and Disorders In The Handmentioning
confidence: 99%